Exploring the Effectiveness of STEAM-Based Courses on Junior High School Students’ Scientific Creativity - Tran, Ngoc-Huy; Huang, Chin-Fei; Hung, Jeng-Fung (Frontiers in Education, 2021)
The purpose of this study is to explore the effectiveness of a STEAM (Science, Technology, Engineering, Arts, Mathematics) -based curriculum on junior high school students’ scientific creativity. The main topic of the STEAM-based curriculum in this study is an ancient mechanical clock that was designed and produced by the authors’ team. Further, the main concept of the ancient mechanical clock is about a gear wheel. Hence, this study designed two stages of courses which were gear wheel science courses (2 weeks) and STEAM-based courses (2 weeks). A total of 62 junior high school students from two different courses participated in this study and were divided into a control group and an experimental group. This study adopted a counterbalance design. The control group joined gear wheel science courses first and joined STEAM-based courses second. In contrast, the experimental group joined STEAM-based courses first. Both groups were asked to complete a pre-test, a middle-test, and a post-test by completing the “Scientific Creativity Test (Cronbach’s α 0.87)”. The results from paired t-test analyses showed that control group students did not show significant differences in scientific creativity before and after joining the gear wheel science courses, but they got significantly higher scores after joining STEAM-based courses than before. On the other hand, the experimental group students got higher scores in scientific creativity after joining STEAM-based courses than before, and persisted in getting higher scores after joining the gear wheel courses than before. Furthermore, the results implied that the STEAM-based courses might help students maintain or continue their scientific creativity. Further discussion is provided.